Asuhan Kebidanan Komprehensif Pada Ny. K Umur 27 Tahun Dengan Anemia Ringan Di PMB Ny. S Wilayah Kerja Puskesmas Kaliwadas Kabupaten Brebes Tahun 2023 - Suji Astuti; Hafsah Hafsah; Surni’ah Surni’ah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The success of maternal and child health can be seen from the indicators of maternal mortality rate (MMR) and infant mortality rate (IMR). One of the causes of maternal mortality is bleeding that occurs due to anemia during pregnancy. Anemia conditions can be prevented by antenatal care (ANC) checks, and can help make labor run physiologically. Objective To provide comprehensive midwifery care to the patient, family, community or closest friends in order to get appropriate care.This study used a qualitative descriptive method with a case study approach. In the first visit pregnancy care found the incidence of Mild Anemia, at the second visit found the incidence of Mild Preeclampsia. In the care of childbirth, there were cases of premature rupture of membranes and chepalopelvic disporpotion so that delivery was carried out by Sectio Caesarea. And in the care of newborns, postpartum and family planning there are no problems and the condition of the mother and baby is normal. Based on the comprehensive care provided to Mrs. K, there were no gaps in the care of pregnancy, puerperium, newborn, and family planning, but in the care of childbirth there were some gaps between theory and practice.